A carbonate platform associated with shallow cold methane seeps in Golfo Dulce, Pacific Costa Rica - Wild, Christian (2015)
Marine methane seeps are typically observed in cold, anoxic and organic-rich deep-sea environments, such as in the Black Sea, where methane emissions fuel the authigenic accretion of calcium carbonate structures via microbial sulphate reduction and anaerobic methane oxidation (Michaelis et al. 2002). For shallow tropical waters, methane seeps are only known from hydrothermal vents (Nakamura et al. 2006). Here, we report about our recent discovery of a cold methane seep in warm (ca. 29℃) and O2-saturated (97-100%) Golfo Dulce (8.496450°N, 83.262610°W) that is located at the Southern Pacific coast of Costa Rica, Central America.